Quality of cryoprotected minced bisugo (Nemipterus spp.) for surimi and minced-based products - Villasenor, Maria Dolor L.; Acevedo, Teresita P. (1995)
The functionality of bisugo mince was maintained during frozen storage with the addition of sucrose and liquid sorbitol at 8% w/w level. Mince cryoprotected with liquid sorbitol and sucrose have myofibrillar proteins comparable to the combined sucrose-liquid sorbitol, which represent the cryoprotectants presently employed by the surimi industry. The choice of sucrose as cryoprotectant to bisugo mince was made on the basis of cost, availability, and current industry formulations of minced and surimi-based products. Sucrose can stabilize the functional properties of frozen bisugo minced when used at 8% w/w level. The level of sucrose can be reduced to 2% w/w, and it can be mixed earlier in the mince to enable processors to stock pile sufficient materials for at least 120 days at -15°C ± 3°. Cryoprotected mince can be used as an alternative starting material or as a new product from for fish balls, quekiam, fish patties, and surimi.
Computer print-out.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Bisugo; Fish as food; Surimi -- Philippines